Employees' experiences of a large-scale implementation in a public care setting: a novel mixed-method approach to content analysis - My Säfström; Ulrika Löfkvist (BMC, 2024)
Abstract Background Research for evidence-based interventions and strategies for implementation continues. Yet there is a continued shortage of qualified health care staff while stress and burnout are common. Health care professionals' individual perceptions towards change needs to be considered to succeed in organisational change. It is therefore relevant to investigate how implementation processes affect employees within the health care sector. Challenges to implementation are especially large in the field of disability care. The present study aims to investigate employees' experiences of an ongoing large-scale implementation, and what they perceived as important to succeed in a complex clinical setting. Methods Semi-structured focus group interviews were conducted with a self-selected sample of employees from a large and complex health care organisation responsible for public disability care in a centrally located Swedish region. A mixed-method approach adapted to content analysis was performed in a three-step process. In the first round, each unit of analysis was selected and then colour coded. In a second round, the coloured units were coded according to content analysis, and categories and concepts were compared and adjusted until the two researchers reached consensus. Finally, to further complement the content analysis, a quantitative analysis of the colour categories was made. Results In general, employees experienced the implementation as being insufficient, yet opinions of the process of implementation were mixed. Most positive experiences were found in relation to the outcomes that the new method had on work effectiveness and patient care. Closely related topics like time constraints, uncertainties concerning the method and the need for supportive functions reoccurred in several concepts suggesting a relationship between differing contextual factors, implementation activities and fidelity. Also evident in the results were the strain on organisational and social work environment and the importance of managers' active leadership. Conclusions Implementation processes are experienced as challenging for employees. Key facilitators are available support functions, clear leadership and time that is sufficient and kept sacrosanct. Leaders need to communicate how and why employees may experience implementation processes differently. The impact that organisational change has on work environment should be considered.